Development of a Distributed Cooperative Vehicles Control Algorithm Based on V2V Communication. (2016) - Zheng, Yi; Jin, Lisheng; Gao, Linlin; Li, Keyong; Wang, Yan; Wang, Faji
Abstract: This paper presents a new distributed Cooperative Vehicles Control (CVC) algorithm without any infrastructure. The algorithm is developed to manipulate individual vehicles' travelling maneuvers based on V2 V communication, so that vehicles can cross the intersection safely and rapidly. Assuming that all vehicles are fully automated, by eliminating the collision probability of vehicles at intersections, the CVC algorithm seeks a safe maneuver for vehicles approaching the intersection and manipulates them. To evaluate the performance of algorithm, we develop an integrated simulation framework. The results show that the CVC algorithm can significantly improve the efficiency of intersection compared with conventional signal control system under varying congestion conditions, moreover, the impact of communication performance on algorithm is also considered.